Canons of Eusebius of Caesarea in The Evangeliarium Anastasiae of the 12th century - Misiarczyk, Leszek (Saeculum Christianum. Pismo Historyczne, 2021)
The article publishes for the first time the famous Canons of Eusebius of Caesarea inscribed in medieval codex called Evangelarium Anastasiae. The comparison between the Canons of Eusebius, included in Evangelarium Anastasiae and the ones from the famous Bible of Płock, confirm the strict dependance between the two indicated codexes. Thanks to two notes on the miracles which took place in the cathedral of Płock in 1148 and have been described in the Bible of Płock we know that the Bible should have been in Płock at this time, so it seems reasonable to suppose that also Evangelarium Anastasiae would have been transcribed in the local scriptorium in the middle of XII century.